Cocompetitive Characteristics and Quantitative Design of Engineering Parameters for Coal Gas Predrainage Boreholes - Tong-qiang Xia; Jiao-fei He; Zi-long Li; Xiao-yan Sun; Dun-shuai Sun; Jian-hang Lu; Hao-jie Cui (Geofluids)
Quantitative design of the optimal gas extraction engineering parameters has always been a key scientific problem to meet the predrainage target of the coal seam, which is paid great attention to and urgently expected to solve for the gas extraction engineering of coal mine. In this paper, the governing equation of the evolution of coal seam gas content is established under the interference and cooperation of gas extraction by boreholes, and the calculation formula of gas cooperative efficiency is defined. Based on gas-air mixed flow, a multifield coupling 3d model of coal gas extraction using boreholes was developed. The content, method, and principle of optimal spacing parameter design of extraction borehole were proposed, and the constraint conditions and objective function of optimal design were constructed. The flow characteristics of gas extraction using boreholes in the coal seam area and the influence of different parameters on gas extraction effect are studied. The cooperative and competitive behaviors of gas extraction by boreholes in coal seam are revealed. The results show that borehole spacing, seam fracture permeability, and gas adsorption constant have significant effects on the synergistic and competitive effects of gas extraction, while the negative pressure of gas extraction and coal matrix permeability have little effects, but the negative pressure of gas extraction has great effects on gas extraction concentration. Finally, Comsol With Matlab is used to solve the multiconstraint nonlinear optimization problem of gas drainage engineering parameters along coal seam in 18401 working face of Tunlan Coal Mine. The effect of actual gas extraction investigation is very remarkable, which provides a quantitative calculation basis for scientific gas extraction in coal mine.